Securing the Future of Information: Digitisation and Preservation of Documents in E-format - Bansal, Alka; Sharma, Vinod Kumari; Kumar, Ashok; Singh, Mohinder (DESIDOC Journal of Library & Information Technology, 2003)
Computers waved a (magic) wand and the whole process creation, access, delivery and preservation of information changed for the literary, scholarly, artistic, scientific and domestic community. Computers transformed the analogue world in to the digital world of 0 and 1. Digitisation came as a most wonderful and welcome tool in hands of libraries, museums, archives, societies, publishers, and others for preserving billions of paper/analogue documents in digital format for retaining their original look as well as with a point of view of their future relevance and potential. Preservation is the activity of protecting something from loss or danger. Digital preservation includes the preservation of print and non print material in digitised form for effective, efficient and purposeful use.Any library can’t digitise all its resources. What should it do? What should it preserve? Why should and for whom should it preserve? How this ever changing digitisation scenario is putting a pressure on librarians/archivists, etc. This paper is making an attempt to seek answers to these questions. This paper also explores the concept of preservation by digitisation, the need of digital preservation, and the problems of digital preservation. How digital preservation activities are being carried out by DESIDOC for its publications: Defence Science Journal, DESIDOC Bulletin of Information Technology, PST Series, etc., are described. A detailed case study of development of database of negatives of photographs taken at various events, being developed by DESIDOC by use of various software like MS Access, Corel Draw, PhotoShop, etc., is discussed. http://dx.doi.org/10.14429/dbit.25.1.3646